출생 시 저체중아와 정상체중아의 유아기 성장과 영양 상태에 관한 연구 - 김혜영(Hye-Young Kim) (Journal of nutrition and health, 2024)
Purpose: This study aimed to investigate the growth status and nutrient intake of children aged 24 to 47.9 months, based on their birth weight, by comparing those born with normal birth weight (NBW, ≥ 2.5 kg) to those with low birth weight (LBW, < 2.5kg). Methods: This cross-sectional study was based on the data of 1,393 children aged 2–3 years from the Korea National Health and Nutrition Examination Survey (2013–2022) conducted by the Korea Disease Control and Prevention Agency. Children were categorized into two groups according to their birth weight. The growth of the children was assessed by measuring their current weight and body mass index (BMI). Dietary intake data were obtained by using the one-day 24-hour recall method. A complex sample logistic regression analysis was performed to examine the association between birth weight categories and early childhood growth, as well as the prevalence of nutrient deficiencies. Results: LBW children were born with an average weight equal to 63% that of NBW children. However, they reached 94.5% of the average weight of NBW children by age 2–3, indicating significant catch-up growth. Despite the observed catch-up growth, LBW children were nearly three times more likely (adjusted odds ratio, 2.963; 95% confidence interval, 1.334–6.581; p < 0.008) to have a BMI below the 5th percentile. On the other hand, essential nutrient intake levels were comparable between the two groups, with no significant differences in the odds of intake below the estimated average requirement (EAR). Conclusion: Although LBW children demonstrated catch-up growth, they remain at a greater risk of undergrowth. Enhanced nutritional strategies, along with broader social and environmental support, are essential for their healthy development during early childhood. KCI Citation Count: 0